Pleistocene mammals from the southern Brazilian continental shelf - Lopes, Renato Pereira; Buchmann, Francisco Sekiguchi [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Fossils of terrestrial mammals preserved in submarine environment have been recorded in several places around the world. In Brazil such fossils are rather abundant in the southernmost portion of the coast, associated to fossiliferous concentrations at depths up to 10 m. Here is presented a review of such occurrences and the first record of fossils in deeper areas of the continental shelf. The fossils encompass several groups of both extinct and extant mammals, and exhibit several distinct taphonomic features, related to the marine environment. Those from the inner continental shelf are removed and transported from the submarine deposits to the coast during storm events, thus forming large konzentrat-lagerstatte on the beach, called "Concheiros". The only fossils from deeper zones of the shelf known so far are a portion of a skull, a left humerus and of a femur of Toxodon sp. and a lower right molar of a Stegomastodon waringi, all collected by fishermen at depths around 20 m. The presence of fossils at great depths and distances from the present coastline, without signs of abrasion and far from areas of fluvial discharges does indicate that these remains have not been transported from the continent to the shelf, but have been preserved directly on the area that today correspond to the continental shelf. These remains indicate the existence of large fossiliferous deposits that have developed during periods of sea-level lowstand (glacial maxima) and have been submerged and reworked by the sea-level rise at the end of the last glaciation. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Megafauna; Pleistocene; Eustasy; Continental shelf; Konzentrat-lagerstatte; Rio Grande do Sul